Outdoor radon and thoron in an area with naturally ventilating bedrock fractures - Haanes, Hallvard; Snook, Paula; Maschler, Alexander; Scheiber, Thomas (Frontiers in Environmental Science, 2025)
Open fractures lead to increased permeability of the bedrock, and, if connected to the surface, allow for groundwater flow and air ventilation. Radon and thoron received by groundwater and ventilating air from bedrock can then be released at the surface. We assessed outdoor levels of radon, thoron and their progeny within the area of Stampa, a rock slope instability in western Norway, characterised by open bedrock fractures and subsurface fracture networks. We used alpha track detectors and in-situ measurements, finding outdoor radon levels of up to 2500 Bq m-3 compared to the global averages of 10 Bq m-3. These outdoor measurements had medians of 70 and 92 Bq m-3 and means of 230 and 280 Bq m-3, which is higher than the maximum recommended indoor radon level of 200 Bq m-3 in Norway. We identified natural ventilation through open fractures as one important source of these enhanced outdoor levels, and another to be transport by groundwater and release at natural groundwater springs. Natural chimney ventilation changes flow direction between warm and cold seasons, and we identified different levels of radon and thoron between different types of fractures suggesting different ventilation intensities and possibly different sizes of subsurface fracture networks.